The associations between working conditions and subjective sleep quality among female migrant care workers - Chen, I-Ming; Lin, Tzu-Yun; Chien, Yi-Ling; Chen, Jennifer Yi-Ying; Chan, Jen-Hui; Liao, Shih-Cheng; Kuo, Po-Hsiu; Chen, Hsi-Chung (Frontiers in Public Health, 2023)
Background: Subjective sleep quality may reflect the mental well-being of migrant care workers; however, the related occupational factors remain unclear. This study examines the association between the characteristics of care labor and the subjective sleep quality of female migrants. Methods: In this cross-sectional study, Southeast Asian migrant care workers in Taiwan were recruited using convenience sampling. Data on working conditions, including workplace setting, wage, working hours, psychiatric symptoms of care recipients, and sleep quality measured using the Pittsburgh Sleep Quality Index (PSQI), were collected through computer-assisted personal interviews. Multiple linear regression analyses were performed to determine the independent relationship between working conditions and the PSQI global score. Results: There were 220 institution-(47.7%) and home-based (52.3%) care workers, and 47.7% had a PSQI score higher than 5. After controlling for covariates, the lowest tertile of wages and daily working hours (> 8 hours) were independently correlated with poor sleep quality. Moreover, in the stepwise regression model, wage and working hours remained the most explainable correlates of poor sleep quality. Conclusions: This study lent support to the imperativeness of improving working conditions on the mental health of migrant care workers.